Gyrfalcons and Ptarmigan in a Changing World 2011
DOI: 10.4080/gpcw.2011.0116
|View full text |Cite
|
Sign up to set email alerts
|

Linking Alaska's Predicted Climate, Gyrfalcon, and Ptarmigan Distributions in Space and Time: A Unique 200-Year Perspective.

Abstract: ABSTRACT.-Gyrfalcons (Falco rusticolus), Rock Ptarmigan (Lagopus muta), and Willow Ptarmigan (L. lagopus) are quintessential Arctic species that are closely linked within the Arctic ecosystem. They likely face similar challenges in the face of rapid changes to their Arctic climate. Gyrfalcons in particular may be most challenged by rapid climate change because of their relatively specialized ecological niche, small population size, and K-selected life history strategy. Given this situation, we were interested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Overall, Arctic peregrine populations now appear stable, with reports of a northward expansion among peregrines in Northwest Greenland (Burnham et al 2012), as well as an advancing timing of breeding in several Arctic regions (Franke 2020), likely as a consequence of climate change. Gyrfalcon populations are also stable, although poaching is an increasing concern in some areas (Potapov 2011), and shrubification and a shrinking High Arctic climate zone may pose challenges in the future, mediated through impacts on their primary prey, ptarmigan (Booms et al 2011). The iconic snowy owl is believed to be declining range-wide, and was recently uplisted by IUCN to a status of vulnerable (Birdlife International 2018).…”
Section: Carnivoresmentioning
confidence: 99%
“…Overall, Arctic peregrine populations now appear stable, with reports of a northward expansion among peregrines in Northwest Greenland (Burnham et al 2012), as well as an advancing timing of breeding in several Arctic regions (Franke 2020), likely as a consequence of climate change. Gyrfalcon populations are also stable, although poaching is an increasing concern in some areas (Potapov 2011), and shrubification and a shrinking High Arctic climate zone may pose challenges in the future, mediated through impacts on their primary prey, ptarmigan (Booms et al 2011). The iconic snowy owl is believed to be declining range-wide, and was recently uplisted by IUCN to a status of vulnerable (Birdlife International 2018).…”
Section: Carnivoresmentioning
confidence: 99%
“…At the population level, long-term monitoring of pre-laying physiological condition could provide insight into how changes in prey availability affect reproduction in Gyrfalcons. Ptarmigan are particularly important prey for Gyrfalcons as they are likely the only source of food available during the pre-laying period (Booms et al 2008(Booms et al , 2011). Moreover, model-based predictions on spatial distribution of Gyrfalcons and both Rock (Lagopus muta) and Willow Ptarmigan (Lagopus lagopus) predict a decrease in the range of these species (Huntley and Green 2011), as well as in the spatial overlap between the Gyrfalcon and their prey over the coming decades (Booms et al 2011) as a result of predicted climate change.…”
Section: Conclusion: Future Research Priorities For Gyrfalconsmentioning
confidence: 99%
“…Ptarmigan are particularly important prey for Gyrfalcons as they are likely the only source of food available during the pre-laying period (Booms et al 2008(Booms et al , 2011). Moreover, model-based predictions on spatial distribution of Gyrfalcons and both Rock (Lagopus muta) and Willow Ptarmigan (Lagopus lagopus) predict a decrease in the range of these species (Huntley and Green 2011), as well as in the spatial overlap between the Gyrfalcon and their prey over the coming decades (Booms et al 2011) as a result of predicted climate change. Concerns for delayed reproduction in Gyrfalcons as a consequence of collapsing ptarmigan abundance cycles in Yukon, Canada, have already been expressed (Mossop 2011).…”
Section: Conclusion: Future Research Priorities For Gyrfalconsmentioning
confidence: 99%
“…Zohmann et al (2013) suggested combining habitat suitability with abundance data of rock ptarmigan from different points in time to evaluate changes in habitat suitability and species distribution over time. Booms et al (2011) assessed changes in rock ptarmigan and gyrfalcon habitat suitability (fundamental niches) over a 200-year time-period and detected substantial environmental changes influencing long-term population viability and predator-prey interactions. Finally, Pedersen et al (2012) stratified survey sites for long-term population abundance monitoring according to habitat with the studies of Unander and Steen (1985) and with rock ptarmigan habitat requirements in other distant parts (e.g.…”
Section: Discussionmentioning
confidence: 99%